Epoxy composites reinforced with nanomaterials and fibres: Manufacturing, properties, and applications - Pooya Parvizi; Milad Jalilian; Karl D. Dearn (Polymer Testing)
Reinforced epoxy composites are an important category of materials that meet industrial needs by addressing the limitations of standard epoxy systems. This review closely examines how different reinforcements, such as fibres (glass, carbon, basalt) and nanofillers (graphene, carbon nanotubes, nanoclay, ceramics), are used either alone or in combination. These reinforcements significantly improve the mechanical properties (like tensile strength and fracture toughness), thermal stability, and electrical conductivity of epoxy composites. The review also discusses advanced fabrication techniques, including chemical vapour deposition and sol-gel processes, while highlighting the significance of achieving uniform dispersion and strong interfacial bonding for optimal composite performance. The results showcase impressive progress in durability, lightweight potential, and multifunctionality, making epoxy composites crucial for high-performance applications in aerospace, automotive, construction, and electronics sectors. Additionally, this review points out existing research gaps, challenges, and future directions that are essential for further advancements in the field.